A checklist of sucking lice (Insecta: Phthiraptera: Anoplura) associated with Mexican wild mammals, including geographical records and a host-parasite list - Sánchez-Montes, Sokani; Guzmán-Cornejo, Carmen; León-Paniagua, Livia; Rivas, Gerardo (Zootaxa, 2013)
A checklist of 44 species of sucking lice (Insecta: Phthiraptera: Anoplura) recorded in Mexico, belonging to nine genera in six families is given, together with a list of the 63 species  of Mexican wild mammal hosts with which they are associated. Summaries of the known geographical records and host relationships for each louse species are presented for each Mexican state. Data were compiled from published and original records, including three new locality records from the states of Oaxaca and Guerrero.